To solve for x, we need to isolate the variable x.
First, distribute the 4 to the terms inside the parentheses:
12x + 8 = 32
Next, subtract 8 from both sides of the equation:
12x + 8 - 8 = 32 - 8
12x = 24
Finally, divide both sides of the equation by 12:
12x/12 = 24/12
x = 2
Therefore, x = 2.
Solve for x.
4(3x + 2) = 32
19 answers
Solve for x.
-2(3x - 15) = 60
-2(3x - 15) = 60
To solve for x, we need to isolate the variable x.
First, distribute the -2 to the terms inside the parentheses:
-6x + 30 = 60
Next, subtract 30 from both sides of the equation:
-6x + 30 - 30 = 60 - 30
-6x = 30
Finally, divide both sides of the equation by -6:
(-6x)/-6 = 30/-6
x = -5
Therefore, x = -5.
First, distribute the -2 to the terms inside the parentheses:
-6x + 30 = 60
Next, subtract 30 from both sides of the equation:
-6x + 30 - 30 = 60 - 30
-6x = 30
Finally, divide both sides of the equation by -6:
(-6x)/-6 = 30/-6
x = -5
Therefore, x = -5.
Solve for x.
5(2x - 8) = -30
5(2x - 8) = -30
To solve for x, we need to isolate the variable x.
First, distribute the 5 to the terms inside the parentheses:
10x - 40 = -30
Next, add 40 to both sides of the equation:
10x - 40 + 40 = -30 + 40
10x = 10
Finally, divide both sides of the equation by 10:
(10x)/10 = 10/10
x = 1
Therefore, x = 1.
First, distribute the 5 to the terms inside the parentheses:
10x - 40 = -30
Next, add 40 to both sides of the equation:
10x - 40 + 40 = -30 + 40
10x = 10
Finally, divide both sides of the equation by 10:
(10x)/10 = 10/10
x = 1
Therefore, x = 1.
Solve for x:
4(3x + 2) + 3 = 35
4(3x + 2) + 3 = 35
To solve for x, we need to isolate the variable x.
First, distribute the 4 to the terms inside the parentheses:
12x + 8 + 3 = 35
Combine the constant terms:
12x + 11 = 35
Next, subtract 11 from both sides of the equation:
12x + 11 - 11 = 35 - 11
12x = 24
Finally, divide both sides of the equation by 12:
12x/12 = 24/12
x = 2
Therefore, x = 2.
First, distribute the 4 to the terms inside the parentheses:
12x + 8 + 3 = 35
Combine the constant terms:
12x + 11 = 35
Next, subtract 11 from both sides of the equation:
12x + 11 - 11 = 35 - 11
12x = 24
Finally, divide both sides of the equation by 12:
12x/12 = 24/12
x = 2
Therefore, x = 2.
Solve for x:
-2(3x - 15) - 4 = 56
-2(3x - 15) - 4 = 56
To solve for x, we need to isolate the variable x.
First, distribute the -2 to the terms inside the parentheses:
-6x + 30 - 4 = 56
Combine the constant terms:
-6x + 26 = 56
Next, subtract 26 from both sides of the equation:
-6x + 26 - 26 = 56 - 26
-6x = 30
Finally, divide both sides of the equation by -6:
(-6x) / -6 = 30 / -6
x = -5
Therefore, x = -5.
First, distribute the -2 to the terms inside the parentheses:
-6x + 30 - 4 = 56
Combine the constant terms:
-6x + 26 = 56
Next, subtract 26 from both sides of the equation:
-6x + 26 - 26 = 56 - 26
-6x = 30
Finally, divide both sides of the equation by -6:
(-6x) / -6 = 30 / -6
x = -5
Therefore, x = -5.
Solve for x:
-4(2x - 11) = 12
Choose an answer from below.
x = 4
x = 2
x = -4
x = -2
-4(2x - 11) = 12
Choose an answer from below.
x = 4
x = 2
x = -4
x = -2
To solve for x, we need to isolate the variable x.
First, distribute the -4 to the terms inside the parentheses:
-8x + 44 = 12
Next, subtract 44 from both sides of the equation:
-8x + 44 - 44 = 12 - 44
-8x = -32
Finally, divide both sides of the equation by -8:
(-8x) / -8 = -32 / -8
x = 4
Therefore, the answer is x = 4.
First, distribute the -4 to the terms inside the parentheses:
-8x + 44 = 12
Next, subtract 44 from both sides of the equation:
-8x + 44 - 44 = 12 - 44
-8x = -32
Finally, divide both sides of the equation by -8:
(-8x) / -8 = -32 / -8
x = 4
Therefore, the answer is x = 4.
Solve for x:
-3(-4x - 3) = -27
Choose an answer from below:
x = 3
x = -3
x = 2
x = -2
-3(-4x - 3) = -27
Choose an answer from below:
x = 3
x = -3
x = 2
x = -2
To solve for x, we need to isolate the variable x.
First, distribute the -3 to the terms inside the parentheses:
12x + 9 = -27
Next, subtract 9 from both sides of the equation:
12x + 9 - 9 = -27 - 9
12x = -36
Finally, divide both sides of the equation by 12:
(12x) / 12 = -36 / 12
x = -3
Therefore, the answer is x = -3.
First, distribute the -3 to the terms inside the parentheses:
12x + 9 = -27
Next, subtract 9 from both sides of the equation:
12x + 9 - 9 = -27 - 9
12x = -36
Finally, divide both sides of the equation by 12:
(12x) / 12 = -36 / 12
x = -3
Therefore, the answer is x = -3.
Solve for x:
2x - 4x - 3 = -27
Choose an answer from below:
x = 12
x = -4
x = -12
x = 4
2x - 4x - 3 = -27
Choose an answer from below:
x = 12
x = -4
x = -12
x = 4
To solve for x, we need to combine like terms and isolate the variable x.
First, combine like terms on the left side of the equation:
-2x - 3 = -27
Next, add 3 to both sides of the equation:
-2x - 3 + 3 = -27 + 3
-2x = -24
Finally, divide both sides of the equation by -2:
(-2x) / -2 = -24 / -2
x = 12
Therefore, the answer is x = 12.
First, combine like terms on the left side of the equation:
-2x - 3 = -27
Next, add 3 to both sides of the equation:
-2x - 3 + 3 = -27 + 3
-2x = -24
Finally, divide both sides of the equation by -2:
(-2x) / -2 = -24 / -2
x = 12
Therefore, the answer is x = 12.
Solve for x:
-4(3x + 10) - 2 = 54
Choose an answer from below:
x = 8
x = 4
x = -8
x = -4
-4(3x + 10) - 2 = 54
Choose an answer from below:
x = 8
x = 4
x = -8
x = -4
To solve for x, we need to isolate the variable x.
First, distribute the -4 to the terms inside the parentheses:
-12x - 40 - 2 = 54
Combine the constant terms:
-12x - 42 = 54
Next, add 42 to both sides of the equation:
-12x - 42 + 42 = 54 + 42
-12x = 96
Finally, divide both sides of the equation by -12:
(-12x) / -12 = 96 / -12
x = -8
Therefore, the answer is x = -8.
First, distribute the -4 to the terms inside the parentheses:
-12x - 40 - 2 = 54
Combine the constant terms:
-12x - 42 = 54
Next, add 42 to both sides of the equation:
-12x - 42 + 42 = 54 + 42
-12x = 96
Finally, divide both sides of the equation by -12:
(-12x) / -12 = 96 / -12
x = -8
Therefore, the answer is x = -8.
Solve for x:
20x - 5(6x + 15) = -45.
Choose an answer from below:
x = -2
x = 3
x = 2
x = -3
20x - 5(6x + 15) = -45.
Choose an answer from below:
x = -2
x = 3
x = 2
x = -3
To solve for x, we need to isolate the variable x.
First, distribute the -5 to the terms inside the parentheses:
20x - 30x - 75 = -45
Combine the like terms:
-10x - 75 = -45
Next, add 75 to both sides of the equation:
-10x - 75 + 75 = -45 + 75
-10x = 30
Finally, divide both sides of the equation by -10:
(-10x) / -10 = 30 / -10
x = -3
Therefore, the answer is x = -3.
First, distribute the -5 to the terms inside the parentheses:
20x - 30x - 75 = -45
Combine the like terms:
-10x - 75 = -45
Next, add 75 to both sides of the equation:
-10x - 75 + 75 = -45 + 75
-10x = 30
Finally, divide both sides of the equation by -10:
(-10x) / -10 = 30 / -10
x = -3
Therefore, the answer is x = -3.